Comparative evaluation of shear bond strength of newer resin cement (RelyX ultimate and RelyX U200) to lithium disilicate and zirconia ceramics as influenced by thermocycling - Rinki Kansal; Sapna Rani; Manoj Kumar; Shalabh Kumar; Gaurav Issar (Contemporary Clinical Dentistry, 2018)
Background/Purpose: The purpose of this study was to compare the shear bond strength of high strength ceramics to cut dentine as influenced by different resin cement types after thermocycling. Materials and Methods: Shear bond strength testing was carried out for 56 sound, freshly extracted first permanent molars. Specimens were divided at random into 2 groups (n = 28) Lithium disilicate and Zirconia. Lithium disilicate and Zirconia specimens were further subdivided depending upon luting with Rely X ultimate cement bonded with single bond universal adhesive and Rely X U200 cement. Half of the specimens of each material luted with cements were subjected to thermocycling. Shear bond strength was evaluated using Universal testing machine at a crosshead speed of 5 mm/min. Results were compared and evaluated using t-test at a significance level of 0.05. The nature of bond failure was observed under a stereomicroscope for each sample. Results: The mean difference of Lithium disilicate test specimens bonded with Rely X ultimate cement bonded with single bond universal adhesive with and without thermocycling was found to be 42.95+/-17.41MPa and 120.62+/-56.46 MPa respectively. The mean difference of Zirconia test specimens with Rely X ultimate cement bonded with single bond universal adhesive, with and without thermocycling, was found to be 8.74+/-2.90 MPa and 164.28+/-43.78 MPa respectively. The mean difference of Lithium disilicate test specimens bonded with Rely X U200 with and without thermocycling was found to be 2.36+/-0.63 MPa and 36.79.62+/-17.21MPa respectively. The mean difference of Zirconia test specimens bonded with Rely X U200 with and without thermocycling was found to be 5.96+/-3.11MPa and 122.46+/-23.01MPa respectively. Conclusion: Zirconia was found to have better shear bond strength than Lithium discilicate. The use of single bond universal adhesive improves bonding to newer higher strength ceramics such as Zirconia. Cohesive failure was predominant at cement dentine interface.